A biomarker of tissue damage, lactate dehydrogenase, is associated with fibulin-1 and oxidative stress in blacks: the SAfrEIC study. (2nd January 2016) - Mokwatsi, Gontse G.; Schutte, Aletta E.; Kruger, Ruan
Abstract: Context : Extracellular matrix (ECM) remodeling and oxidative stress is present in hypertension and associated arterial stiffness, but little is known on the physiological link among lactate dehydrogenase (LDH), fibulin-1, and reactive oxygen species (ROS). Objective : The objective of this study is to explore the link among a marker of tissue damage (LDH), fibulin-1 (as ECM biomarker), and ROS. Methods : We included 316 black and 305 white South Africans and determined the above-mentioned biomarkers along with additional cardiometabolic risk factors. Results : LDH associated positively with fibulin-1 ( β  = 0.23; p  < 0.001) and ROS ( β  = 0.11; p  = 0.30) in blacks only. Conclusion : Our finding suggests that increased circulating levels of LDH may be due to early ECM remodeling and oxidative stress in blacks that are subjected to detrimental and uncontrolled lifestyle risk factors.